The Urgent Need to Reform Outdated Regional Regulations on Public Order : (An Examination of Kapuas Hulu Regency's Public Order Regional Regulations from 1978) - Hazdan, Muhammad Fahmi; Yenny Aman Serah; Temmy Hastian (Fakultas Hukum Universitas Islam Jakarta, 2025)
Maintaining public order is one of the responsibilities of both the central and regional governments. The Regional Government of Kapuas Hulu Regency still relies on legal foundations in force since 1978 to maintain public order. This research aims to examine the validity of the Regional Regulation of Kapuas Hulu Regency Number 9 of 1978 concerning the Implementation of Cleanliness and Public Order and to analyze the urgency of establishing a new regional regulation on public order in Kapuas Hulu Regency. This study employs normative legal research methods with a statutory approach focused on vertical and horizontal synchronization. The results of the research indicate two main issues in the implementation of the regulation. First, there is a discrepancy between the legal basis of the 1978 Regional Regulation, namely Law Number 5 of 1974, and the currently prevailing legislation (Law Number 23 of 2014), which grants broader autonomy to regional governments. Second, several public order issues emerging within the community have not been accommodated in the substance of the existing Regional Regulation. Based on these findings, it is concluded that there is an urgent need to update the Regional Regulation of Kapuas Hulu Regency on Public Order to align with meaningful participation mechanism.